Helping spanish SMEs staff to develop their competence in writing business letters - Foz-Gil, Carmen; González-Pueyo, Isabel (International Journal of English Studies, 2009)
This paper reports on the development of a website tool aimed at helping Spanish small and medium enterprises (SMEs) staff to write their commercial correspondence in English. It describes the steps involved in the tool system design process, making an emphasis on the methodological criteria and rational that guided us to develop the site. In order to obtain the material, a corpus of commercial correspondence written in English was collected and later analysed, applying a genre-based approach as established by Bhatia (1993) and Swales (1990). The findings provided the move structure and strategies of each type of letter as well as the lexico-grammatical realizations of each move which later would be standardised and presented to be used systematically in the composition of letters with the same communicative purpose. This work illustrates how a genre-based approach can successfully be applied to ESP materials development.